Perlindungan Hukum Terhadap Anak Korban Perundungan (Bullying) - Manilani, Flora Apriliana; Medan, Karolus Kopong; Fanggi, Rosalind A (Law Faculty, Nusa Cendana University, 2025)
Bullying prone to occur in the community, especially children, bullying occurs in various forms such as verbal, physical violence and also cyberbullying. In Indonesia the act of bullying is not explicitly regulated in legislation. The problem discuss in this research is how the legal arrangements for criminal acts of bullying against children according to Indonesian legislation and the form of legal protection for child victims of criminal acts of bullying. The aim is to be able to know and explain the legal arrangements of bullying against children and what forms of protection the law provides for child victims of bullying in Indonesian legislation.The researchers used normative research, wich uses a conceptual and legislative approach to describe and analyse the problems found. The results of this study indicate that act of bullying in criminal law is not specifically regulated, so it is necessary to pay attention to the type of bullying in order to determine the right laws and regulation. In terms of protection of bullying victims, criminal laws only regulate the victim's right to receive restitution or compensation, but do not regulate specific rights to the psychological protection of victims. From the research result, it can be concluded that bullying is generally defined as an act of violence which is then futher described into several forms of criminal acts in statutory provisions, so that in order to protect society from bullying,several legal protection efforts are made, including preventive, preemptive, and repressive legal protection.